PEMILIHAN MUSTAHIQ PADA MASJID AL-ADZKAR DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Mardiyati, Sri; Ningsih, Retna; Hidayatulloh, Reko Syarif (Journal of Research and Publication Innovation, 2024)
This research focuses on the use of the Simple Additive Weighting (SAW) method to evaluate and determine the priorities of the most worthy zakat recipients at the Al-Adzkar Mosque. The SAW method, a decision-making technique based on weights that involves adding up attribute scores, is used to assess mustahiq candidates based on predetermined criteria. These criteria usually include factors such as economic status, number of family members, health conditions, education level, and other relevant aspects. Each criterion is given a certain weight to indicate its level of significance, and candidates are evaluated based on these criteria to calculate a total score using the SAW formula. The final result of this research is to categorize mustahiq candidates based on their cumulative scores, and individuals who obtain the highest scores are considered the most deserving zakat recipients. The abstract may also include a brief overview of the social and practical consequences of applying the SAW approach in this particular situation, as well as the efficacy of this method in increasing the objectivity and transparency of mustahiq selection procedures.